2019
DOI: 10.1016/j.rbmo.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Does theFMR1 gene affect IVF success?

Abstract: Published research suggests that women who carry the FMR1 premutation (about 55 to 200 CGG) may have reduced success with IVF, e.g. fewer retrieved oocytes after ovulatory stimulation regimens. A meta-analysis has revealed no association within subcategories of normal repeat length (<45 CGG) and IVF pregnancy rates. ABSTRACTFMR1 CGG trinucleotide repeat expansions are associated with Fragile X syndrome (full mutations) and primary ovarian insufficiency (premutation range); the effect of FMR1 on the success of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In addition, a recent review suggested that women with FMR1 premutation should be informed that they might have lower chances of success with in vitro fertilization (IVF) due to lower number of retrieved oocytes after ovulatory stimulation regimens; interestingly, IVF outcomes are apparently unaffected by FMR1 repeat lengths smaller than 55 CGG or greater than 200 CGG (Pastore et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a recent review suggested that women with FMR1 premutation should be informed that they might have lower chances of success with in vitro fertilization (IVF) due to lower number of retrieved oocytes after ovulatory stimulation regimens; interestingly, IVF outcomes are apparently unaffected by FMR1 repeat lengths smaller than 55 CGG or greater than 200 CGG (Pastore et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They don’t have any distinctive physical features or intellectual disabilities which allow the identification of their PM carrier status. Furthermore, due to the decreasing number of extracted eggs and the need for higher doses of gonadotropin hormone, compared to women without the PM or even with the FM; PM carriers have a lower success rate in IVF protocols ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The egg receptor for this case had two previous failed attempts of IVF with her own eggs; she was the donor´s sister and was also a PM carrier. This enhances the need for young women with PM for FXS, even without a reproductive desire, to undergo ovarian reserve tests and in case of a decreased reserve be offered fertility preservation alternatives ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Women carrying midrange repeats (approximately 70–90 repeats) have the highest risk for POI, while carriers of smaller and larger premutation repeat lengths have an increased risk of POI compared to the general population, but not to the same extent as mid-range carriers. It remains contentious whether normal or grey zone CGG repeat lengths are correlated with ovarian reserve parameters, age at natural menopause and IVF outcome ( Gleicher et al , 2009 ; Gleicher et al , 2011 ; Voorhuis et al , 2013 ; Gustin et al , 2015 ; Banks et al , 2016 ; Pastore et al , 2019 ). In addition, X chromosome inactivation ( Sullivan et al , 2005 ; Tejada et al , 2008 ; Spath et al , 2010 ), background genes ( Hunter et al , 2008 ; Spath et al , 2011 ) and smoking ( Spath et al , 2011 ) have all been investigated to explain the incomplete penetrance of POI among premutation carriers.…”
Section: Fragile X-associated Premature Ovarian Insufficiencymentioning
confidence: 99%